2021
DOI: 10.3390/nu13113902
|View full text |Cite
|
Sign up to set email alerts
|

Per- and Polyfluoroalkyl Substance Exposure Combined with High-Fat Diet Supports Prostate Cancer Progression

Abstract: Per- and polyfluoroalkyl substances (PFAS) are synthetic chemicals utilized in various industrial settings and include products such as flame retardants, artificial film-forming foams, cosmetics, and non-stick cookware, among others. Epidemiological studies suggest a link between increased blood PFAS levels and prostate cancer incidence, but the mechanism through which PFAS impact cancer development is unclear. To investigate the link between PFAS and prostate cancer, we evaluated the impact of metabolic alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 55 publications
0
19
0
Order By: Relevance
“…Additionally, recent studies have reported PFAS-mediated alterations of epigenetic regulators, such as DNA methyltransferases, ten-eleven translocation methylcytosine dioxygenases, and histone deacetylase enzymes in different mouse organs and human cell lines [ 106 , 107 , 110 , 117 , 118 , 119 ]. PFAS-mediated effects on histone modifications and microRNAs have also been described [ 49 , 106 , 107 , 118 , 120 , 121 , 122 ].…”
Section: Potential Mechanisms Of Pfas Carcinogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, recent studies have reported PFAS-mediated alterations of epigenetic regulators, such as DNA methyltransferases, ten-eleven translocation methylcytosine dioxygenases, and histone deacetylase enzymes in different mouse organs and human cell lines [ 106 , 107 , 110 , 117 , 118 , 119 ]. PFAS-mediated effects on histone modifications and microRNAs have also been described [ 49 , 106 , 107 , 118 , 120 , 121 , 122 ].…”
Section: Potential Mechanisms Of Pfas Carcinogenesismentioning
confidence: 99%
“…Of note, these actions are mediated, in part, through PPARα, providing the potential for enhanced tumor promotion. We recently showed that PFOS exposure and a high-fat diet synergize to increase prostate cancer xenograft growth in mice [ 122 , 162 ]. PFOS treatment increased glucose metabolism and pyruvate production in prostate cancer cells [ 122 ].…”
Section: The Case For Prostate Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Histone 3 displays altered acetylation at lysine 4, 9, and 27 in breast cancer cells that fail to respond to ER antagonists (65)(66)(67). Systemic metabolic changes impact hormone-dependent cancer cell metabolism (41,68) and composition of histone marks (39,69), and response to therapies (19,41). Our findings suggest an altered ERα activity in MBC cells residing in the liver microenvironment, and a role for metabolic and epigenetic enzymes to interact with ER in a Fulv-dependent manner to locally change epigenetic marks, which would lead to altered response to ERα antagonists.…”
Section: Discussionmentioning
confidence: 99%
“…To visualize the separation between No ECM and Liver ECM groups' metabolic profiles VIP scores for the top 25 metabolites that discriminated between treatment groups were calculated and displayed using the Partial least squares discriminant analysis (PLS-DA) tool. Enrichment analysis and pathway analysis were used to identify metabolic pathways associated with enriched metabolites (fold change >2 or <0.05) as previously described (39)(40)(41)(42).…”
Section: Metabolomics Analysismentioning
confidence: 99%